The influence of social support on the wellbeing of immigrants residing in Italy: Sources and functions as predictive factors for life satisfaction levels, sense of community and resilience. (January 2023) - Novara, C.; Martos-Méndez, M.J.; Gómez-Jacinto, L.; Hombrados-Mendieta, I.; Varveri, L.; Polizzi, C.
Abstract: Moving from one country to another involves not only separation from the country of origin, but also the tiring process of integration into a new physical, institutional, and sociocultural context, which may expose migrants to acculturation stress. The loss of former support networks, or at the very least their transformation, presents immigrants with the need to rebuild their social support systems in the host country, involving an active search for support. Therefore, the aim of study is to analyze the structure of informal social support and its capacity to predict immigrants' sense of community, resilience, and satisfaction with life. The results confirm that social support predicts satisfaction with life, sense of community, and resilience. Our findings highlight the way sources and frequency of support, and the satisfaction with which they are associated, have different degrees of predictive value on the dependent variables under investigation. In this study, it can be concluded that social support is an important factor in the well-being of migrants and their integration into the host community. The results have an important practical value in promoting interventions that improve immigrants' support networks and, consequently, increase their satisfaction with life, sense of community, and resilience.